2003
DOI: 10.1079/joh2003186
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of the optic nerve as a migration route for larvae in ocular toxocariasis of Mongolian gerbils

Abstract: Although Toxocara canis, an important pathogen of ocular disease, tends to migrate to the eye, the precise migratory route has yet to be determined experimentally. Mongolian gerbils, Meriones unguiculatus, known as a useful animal model for human toxocariasis, were used to investigate the migration route toward the eyes. Infective larvae of T. canis were directly inoculated into the intracranial region. Haemorrhagic lesions or larvae were observed in 56.3% of cases. Histopathologically, a larva was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
(22 reference statements)
0
11
0
1
Order By: Relevance
“…Hayashi et al (115) observed that the migratory route of T. canis larvae to the eye may be from the brain through the optic nerve, as assessed in one experimental study using a gerbil animal model (although the gerbil is not a natural paratenic host of T. canis). Other researchers postulated that it is more likely that larvae travel in blood vessels rather than by burrowing and that the route by which larvae reach the eye remains to be determined (103).…”
Section: Ocular Toxocariasismentioning
confidence: 99%
See 1 more Smart Citation
“…Hayashi et al (115) observed that the migratory route of T. canis larvae to the eye may be from the brain through the optic nerve, as assessed in one experimental study using a gerbil animal model (although the gerbil is not a natural paratenic host of T. canis). Other researchers postulated that it is more likely that larvae travel in blood vessels rather than by burrowing and that the route by which larvae reach the eye remains to be determined (103).…”
Section: Ocular Toxocariasismentioning
confidence: 99%
“…While our understanding of the mechanisms underlying human NT is incomplete, seroepidemiological surveys demonstrate high levels of exposure to Toxocara in the population, suggesting that NT may be an underestimated public health implication of infection (36). Recently, Toxocara was described as "America's most common neglected infection of poverty and a helminthiasis of global importance" (115,122); however, the number of cases of NT will tend to be underestimated due to nonspecific clinical signs compared with VLM, as well as due to a lack of availability of appropriate testing, thus leading to possible underdiagnosis (18,122).…”
Section: Neurotoxocariasismentioning
confidence: 99%
“…Dubey [17] showed larval migration patterns of T. cati in mice. In other previous studies, it was proved that Mongolian gerbils could be a paratenic host for T. cati , which may result in ocular larva migrans and neurotoxocariasis [18,21]. The present study presents further information on the experimental infection of Mongolian gerbils and Wistar rats with T. cati and larval recovery at different times of infection.…”
mentioning
confidence: 50%
“…The animals were maintained under standard conditions, in an environment with controlled temperature and humidity. Each animal in the experimental groups was intubated with approximately 240 and 2,500 embryonated T. cati eggs, respectively [18,21,22]. The eggs were derived from adult female worms and were embryonated according to our previous paper [23].…”
mentioning
confidence: 99%
“…Introducción E l compromiso de nervios craneales por larva migrans de Toxocara canis es sumamante inusual y casi exclusivamente afecta al nervio óptico 1 . No ha sido descrita la afectación del séptimo nervio craneal asociada a larva migrans de T. canis.…”
unclassified